Clinico-Radiological-Pathological Correlation of Visual Loss in COVID-Associated Rhino-Orbito-Cerebral Mucormycosis. Issue 3 (11th May 2022) - Goel, Ruchi; Arora, Ritu; Shah, Shalin; Chhabra, Mohit; Kumar, Jyoti; Khurana, Nita; Gupta, Swati; Khanam, Samreen; Kumar, Sumit; Singh, Sonam; Meher, Ravi; Thakar, Meenakshi; et al.
Abstract : Purpose: To correlate the clinical, radiological, and histopathological features in Covid-associated Rhino-orbito-cerebral mucormycosis cases presenting with acute visual loss. Design: Cross-sectional study. Methods: Covid-associated Rhino-orbito-cerebral mucormycosis cases with unilateral visual loss, planned for exenteration, underwent orbital and ophthalmological ocular examination. The available radiological sequences, doppler ultrasonography and histopathology findings were correlated with clinical manifestations. Results: The median age was 51 years and the male: female ratio was 3:1. All except one presented with unilateral ophthalmoplegia. The ocular media were hazy in 2 eyes. In 8 eyes, retinal changes were suggestive of occlusion of CRA (6), combined occlusion of CRA and central retinal vein (1), and myopic degeneration with hypertensive retinopathy (1). The contralateral eye showed retinal ischemic changes in one patient. Radiological imaging showed orbital apex involvement in the 10 affected eyes and one contralateral eye. Ipsilateral cavernous sinus thrombosis, diffusion restriction on MRI of optic nerve, internal carotid artery narrowing/thrombosis, and cortical watershed infarcts were seen in 8, 4, 4, and 2 cases, respectively. The blood flow in CRA and ophthalmic artery was absent or reduced in all the 10 affected eyes and in 1 contralateral eye. On histopathology, orbital fat necrosis, fungal hyphae, acute inflammation, granuloma formation, ischemic thrombosis of ophthalmic artery was observed in 10 specimens. CRA was patent in 9 and thrombosed in 1 eye. Optic nerve was ischemic in 8 and viable in 2 eyes. Conclusion: Acute visual loss in ROCM cases is associated with orbital apex involvement and thrombotic ischemia of ophthalmic artery. Cessation of flow in CRA possibly occurs secondary to ophthalmic artery thrombosis. Abstract : The clinical features, blood flow velocities of Ophthalmic artery and Central Retinal Artery and CT/MRI findings were correlated with histopathology of exenterated orbits in COVID- associated Rhino-orbito-cerebral mucormycosis patients presenting with acute loss of vision.